HUBUNGAN EFEKTIVITAS PROGRAM LAYANAN SIM ONLINE DENGAN KEPUASAN MASYARAKAT DI POLRESTA PADANG - Najma Hayati; Nora Eka Putri (Ensiklopedia Social Review, 2020)
This research is motivated by a few people who understand about the Online SIM Program, the lack of socialization by the Padang Police regarding the Online SIM Program and the public's knowledge of the intentions and procedures for administering SIM Online. The internet network is slow so that it hinders the network with Korlantas Polri so that it affects the community satisfaction index has not been carried out regularly. This study aims to determine whether or not there is a relationship between the effectiveness of the SIM Online service program and community satisfaction at the Padang Police and to find out how far the effectiveness of the Online SIM service program is related to community satisfaction at the Padang Police. The type of research used is descriptive quantitative research, namely quantitative research which aims only to describe the state of social symptoms as they are, without looking at the existing relationships. The sample in this study was focused on two-wheeled motorcycle users in the city of Padang, totaling 100 using purposive random sampling technique using simple correlation analysis. Based on the results of data analysis in the research that has been carried out, it is concluded that there is a significant positive correlation between the effectiveness of the Online SIM Service program with community satisfaction at the Padang Police. This means that the higher the program effectiveness score, the higher the community satisfaction or the better the effectiveness of the SIM Online service program, the higher the community satisfaction.